Narration of Ikrar Kajat in Gondowangi Village: Documentation of Formula Oral Literature of Kawi Mountain - Teguh Tri Wahyudi; Maryaeni Maryaeni; Fandy Romadhoni; Ahmad Junaidi (Jurusan Sastra Indonesia, 2017)
This article is based on the results of oral literature research on the slopes of Kawi. Object presented is the ikrar kajat conducted by Mbah Ngari, one of the speakers of oral tradition in the village of Gondowangi in Wagir district. Verbal data was collected using field research methods, interview techniques and video documentation. Data analysis is focused on studying the formula ikrar kajat. The result is video documentation that has been completed by subtitles. The greeting and demand formula is the main element in the pledge narrative.